Simultaneous removal of tetracycline and norfloxacin from water by iron-trimesic metal-organic frameworks. Issue 3 (June 2022) - Zhou, Yi; Fang, Fei; Lv, Quankun; Zhang, Yan; Li, Xuede; Li, Jie
Abstract: Antibiotics removal from pharmaceutical wastewater has recently been more and more urgent from the perspective of human health and sustainable environment development. Simultaneously removal of multiple antibiotics from the wastewater is of great significance because various kinds of antibiotics are usually coexist. Metal-organic frameworks (MOFs), such as low-cost and environmentally friendly Fe-BTC can serve as promising adsorbents for the removal of antibiotic pollutants from water. In this study, Fe-BTC can effectively remove tetracycline (TC) and norfloxacin (Nor) in both single- and binary-pollutant systems. The adsorption capacity of Fe-BTC for TC and Nor are 714.3 and 346.6 mg/g, respectively. Although the adsorption capacity of the competitive system decreased, it still reached 682.5 mg/g and 334.6 mg/g, respectively, which are larger than most of the studies that have been reported for the removal of antibiotics by MOFs. In addition, in the lake water samples contaminated with TC and Nor as well as different simulated water samples, the performance of the material was well maintained. Fe-BTC exhibited high adsorption performance in a broad pH range, as well as under the interference of various ions and natural organic matter, indicating an unprecedented selectivity. In addition, Fe-BTC showed excellent recycling ability. According to the results of batch adsorption experiments and microscopic characterization, the adsorption mechanism of TC and Nor on Fe-BTC is mainly attributed to the coordination, pore filling, and π-π stacking. Overall, our research suggests that Fe-BTC might be a promising material for treating wastewater polluted with complicated antibiotic combinations. Graphical Abstract: ga1 Highlights: Tetracycline (TC) and norfloxacin (Nor) adsorption by Fe-BTC were studied systematically in both single and binary systems. The adsorption capacity of TC and Nor were 714.3 and 334.6 mg/g, respectively. Fe-BTC showed superior anti-interference ability and high reusability for TC and Nor. Fe-BTC was efficient in the removal of TC and Nor from various contaminated synthetic water samples. Mechanisms including coordination, pore filling, and π-π stacking contributed to TC and Nor adsorption by Fe-BTC.